Pengembangan Modul Ajar Konsep Taksonomi Tumbuhan Mangrove untuk Mata Kuliah Keanekaragaman Tumbuhan di Program Studi Pendidikan Biologi Universitas Papua - Semuel Sander Erari; Hengky Lukas Wambraw (STKIP HARAPAN BIMA, 2026)
This study aims to produce a valid and practical teaching module for the concept of mangrove plant taxonomy in Saubeba Bakau Bay, Manokwari City. The research method is Research and Development (R D). This study uses the ADDIE model with stages of Analysis, Design, Development, Implementation and Evaluation. Mangrove diversity data was collected by exploration and documentation methods, validity and practicality data were obtained from material experts, media experts, lecturers' and students' responses. To determine the percentage of validity and practicality of the module, the results were obtained from the calculation of the total score obtained divided by the maximum score multiplied by one hundred percent. The results showed that there were three types of mangrove plants found in Saubeba Bakau Bay: Avicennia alba, Rhizophora apiculata and Sonneratia alba. The results of the validation of the teaching module based on media experts showed that the developed module was very feasible with an average percentage value of 84%. The results of the assessment based on material experts obtained an average percentage value of 96% with a very feasible category. The results of the lecturer response assessment obtained an average percentage of 96.5% with a very practical category. The results of the student response assessment obtained an average percentage of 93%, indicating that it was very practical. Therefore, the developed teaching module is very feasible and practical, making it suitable for use in the learning process.